DHb9 expressing larval motor neurons persist through metamorphosis to innervate adult‐specific muscle targets and function in Drosophila eclosion. Issue 12 (6th June 2016) - Banerjee, Soumya; Toral, Marcus; Siefert, Matthew; Conway, David; Dorr, Meredith; Fernandes, Joyce
ABSTRACT: The Drosophila larval nervous system is radically restructured during metamorphosis to produce adult specific neural circuits and behaviors. Genesis of new neurons, death of larval neurons and remodeling of those neurons that persistent collectively act to shape the adult nervous system. Here, we examine the fate of a subset of larval motor neurons during this restructuring process. We used a dHb9 reporter, in combination with the FLP/FRT system to individually identify abdominal motor neurons in the larval to adult transition using a combination of relative cell body location, axonal position, and muscle targets. We found that segment specific cell death of some dHb9 expressing motor neurons occurs throughout the metamorphosis period and continues into the post‐eclosion period. Many dHb9 > GFP expressing neurons however persist in the two anterior hemisegments, A1 and A2, which have segment specific muscles required for eclosion while a smaller proportion also persist in A2–A5. Consistent with a functional requirement for these neurons, ablating them during the pupal period produces defects in adult eclosion. In adults, subsequent to the execution of eclosion behaviors, the NMJs of some of these neurons were found to be dismantled and their muscle targets degenerate. Our studies demonstrate a critical continuity of some larval motor neurons into adults and reveal that multiple aspects of motor neuron remodeling and plasticity that are essential for adult motor behaviors. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1387–1416, 2016